FIR to FIR Model Reduction with Linear Group Delay in Passband by SDP Optimization. (20th February 2020) - Hu, Haijiang; Song, Shaojing; Zhang, Fengdeng
Abstract : Filter model reduction is an important optimization method in digital signal processing. A method of FIR to FIR model reduction using SDP optimization is proposed in this paper. At first, we use SDP to design an original FIR filter. Then we name a general K -order FIR digital filter H 1 z − 1 with coefficient values equal to the first K + 1 filter coefficient values of H 0 z − 1 . Finally, we design a new general K -order FIR digital filter H 2 z − 1 connected in parallel with H 1 z − 1 using SDP optimization. The experiment results show this method has good performance on the magnitude error and the linear phase in passband. Therefore, this method can be used in the field of digital signal processing.